2011
DOI: 10.1007/s10803-011-1384-9
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Autism Spectrum Disorders in the General Practitioner’S Practice

Abstract: It takes considerable time before Autism Spectrum Disorders are diagnosed. Validated diagnostic instruments are available, but not applicable to primary healthcare. By means of a case–control study we investigated whether there were differences in presented complaints and referral patterns between children with ASD (n = 49) and a control group of children without ASD (n = 81). Children with ASD were often presented as crybabies and often showed feeding problems. They visited the GP’s surgery more often with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
0
13
0
2
Order By: Relevance
“…This hypothesis is supported by findings from adult brain scans, as these scans show how listening to crying from infants with ASD activate a brain activity that indicates far more negative emotions than does listening to the sound of typically developing infants’ crying (Venuti et al., ). In the present study, the crying of children with ASD may have been experienced by the mother as lasting longer, which again could have triggered that a higher proportion of children with ASD were described as “crybabies” in studies based on information from primary healthcare (Barnevik Olsson et al., ; van Tongerloo et al., ).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This hypothesis is supported by findings from adult brain scans, as these scans show how listening to crying from infants with ASD activate a brain activity that indicates far more negative emotions than does listening to the sound of typically developing infants’ crying (Venuti et al., ). In the present study, the crying of children with ASD may have been experienced by the mother as lasting longer, which again could have triggered that a higher proportion of children with ASD were described as “crybabies” in studies based on information from primary healthcare (Barnevik Olsson et al., ; van Tongerloo et al., ).…”
Section: Discussionmentioning
confidence: 67%
“…A study based on prospective data from the ALSPAC cohort compared children who were later diagnosed with ASD with children from the cohort and found no statistically significant differences in the crying pattern at 6 and 18 months (Bolton, Golding, Emond, & Steer, ). However, two studies based on records from primary healthcare showed that children who were later diagnosed with ASD were described as excessively crying in infancy more often than did other children (Barnevik Olsson et al., ; van Tongerloo, Bor, &; Lagro‐Janssen, ). Other deviations in regulation of emotions also have been shown in the first years of life in children who are later diagnosed with ASD.…”
mentioning
confidence: 99%
“…In some children with ASDs there is an early onset of regulatory problems (Barnevik-Olsson et al, unpublished data, 2013), such as with sleeping,60 crying,61 and feeding 62. The importance of identifying autism at an early age has been stressed in many studies 63,64.…”
Section: Early Symptoms Screening and Diagnosismentioning
confidence: 99%
“…Children with developmental delays have higher rates of health care use, yet paradoxically, are more likely to have unmet health needs . More specifically, children with ASD are more likely to have chronic illnesses and are more likely than their counterparts to have otorhinolaryngology conditions . A 2013 literature review reported on several studies that illustrated comorbidities found in children with ASD, including higher rates of psychiatric disorders (eg, anxiety) and feeding disorders .…”
Section: Literature Reviewmentioning
confidence: 99%
“…4 More specifically, children with ASD are more likely to have chronic illnesses and are more likely than their counterparts to have otorhinolaryngology conditions. 5,6 A 2013 literature review reported on several studies that illustrated comorbidities found in children with ASD, including higher rates of psychiatric disorders (eg, anxiety) and feeding disorders. 7 Children with ASD are more likely to be diagnosed with sleep disordered breathing and to undergo surgery to correct this problem (relative risk: 1.5).…”
Section: Literature Reviewmentioning
confidence: 99%